Microbiome in Blood Samples From the General Population Recruited in the MARK-AGE Project: A Pilot Study - D’Aquila, Patrizia; Giacconi, Robertina; Malavolta, Marco; Piacenza, Francesco; Bürkle, Alexander; Villanueva, María Moreno; Dollé, Martijn E. T.; Jansen, Eugène; Grune, Tilman; Gonos, Efstathios S.; Franceschi, Claudio; Capri, Miriam; et al. (Frontiers in Microbiology, 2021)
The presence of circulating microbiome in blood has been reported in both physiological and pathological conditions, although its origins, identities and function remain to be elucidated. This study aimed to investigate the presence of blood microbiome by quantitative real-time PCRs targeting the 16S rRNA gene. To our knowledge, this is the first study, in which the circulating microbiome has been analysed in such a large sample of individuals since the study was carried out on 1285 Randomly recruited Age-Stratified Individuals from the General population (RASIG) from several different European countries recruited within the EU Project MARK-AGE in which a series of clinical biochemical parameters were determined. The results obtained reveal an association between microbial DNA copy number and geographic origin. By contrast, no gender and age-related difference emerged, thus demonstrating the role of the environment in influencing the above levels independent of age and gender at least until the age of 75. In addition, a significant positive association was found with Free Fatty Acids (FFA) levels, leukocyte count, insulin, and glucose levels. Since these factors play an essential role in both health and disease conditions, their association with the extent of the blood microbiome leads us to consider the blood microbiome as a potential biomarker of human health.